Predicting moisture content of long length log piles of Eucalyptus urophylla under outdoor storage - de Jesus Eufrade-Junior, Humberto [UNESP]; Rodrigues, Sérgio Augusto [UNESP]; Spadim, Emanuel Rangel [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Ballarin, Adriano Wagner [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
The main objective of this work was to adjust moisture prediction models for logwood piles (6.2 m of length) of Eucalyptus urophylla stocked during two storage periods- a dry season and a rainy season - in the center-south of the State of São Paulo. For this purpose, the moisture content was indirectly estimated by daily weighing of the logs on fixed scales designed for this purpose during 160 days of storage. In the development of the equations, the multiple linear regression technique was used with stepwise selection of variables. The moisture prediction models showed that the variables, relative air humidity and number of days (storage time), can be used to estimate the moisture content of the wood (R2aj.> 92%). The logs stocked during the period called dry season in the study region (542 mm of rain) showed a lower final moisture content - 31.1% (wet basis) in relation to the logs stored in the rainy season (919 mm of rain) with final moisture content of 36.4% (wet basis).
Predição do teor de umidade de toras longas de madeira de Eucalyptus urophylla estocadas em pilhas ao ar livre
Keywords: Air-drying; Eucalyptus urophylla; Meteorological variables; Seasons of the year